Immunomagnetic B cell isolation as a tool to study blood cell subsets and enrich B cell transcripts - Amanda N. Henning (BMC, 2021)
Abstract Objective Transcriptional profiling of immune cells is an indispensable tool in biomedical research; however, heterogenous sample types routinely used in transcriptomic studies may mask important cell type-specific transcriptional differences. Techniques to isolate desired cell types are used to overcome this limitation. We sought to evaluate the use of immunomagnetic B cell isolation on RNA quality and transcriptional output. Additionally, we aimed to develop a B cell gene signature representative of a freshly isolated B cell population to be used as a tool to verify isolation efficacy and to provide a transcriptional standard for evaluating maintenance or deviation from traditional B cell identity. Results We found RNA quality and RNA-sequencing output to be comparable between donor-matched PBMC, whole blood, and B cells following negative selection by immunomagnetic B cell isolation. Transcriptional analysis enabled the development of an 85 gene B cell signature. This signature effectively clustered isolated B cells from heterogeneous sample types in our study and naïve and memory B cells when applied to transcriptional data from a published source. Additionally, by identifying B cell signature genes whose functional role in B cells is currently unknown, our gene signature has uncovered areas for future investigation.